Worship and spirituality as a praxis-orientated apologetic in a post-modern world (the New Age) - an incarnational engaged approach - EK Foshaugen (Acta Theologica)
This article highlights certain tenets of postmodernism and then attempts to provide an evangelical Christian response. Postmodern ideology and its religious face as reflected in the New Age movement need not cause disquietude or be derided. Rather, postmodern thought should be allowed to challenge any premodern fundamentalism and modern rationalism char the evangelical Church has uncritically internalised or embraced. Postmodernism provides an incredible opportunity to develop new methods to demonstrate the Gospel message of love and hope. In this article it is argued that this is best done through the supernatural power of an incarnational, engaged worship and spirituality (of adoration and action). Then, uncondidonal and sacrificial love is demonstraced as a praxis-orientated apologetic through the Christian's life-story. Christian truth claims need to be authenticated, convictions must be acted out, to provide plausibility, persuasion, incentive and inducement in a pluralistic and relativistic postmodern world that is aware and hungers after spirituality.